The Influence of Civil Law on the Quality of Community Life: Case Studies in Big Indonesian Cities - Achmad Fitrian; Dodi Rusmana; Ning Adiasih; , Marjan Miharja; Nabain Idrus (Universitas Ekasakti, 2024)
This research project aims to examine the influence of civil law on the quality of life of people in big cities through a comprehensive literature review. The role of civil law in maintaining the equilibrium between the rights and obligations of individuals in a complex urban society is of great consequence. This research identifies the ways in which the application of civil law in the areas of property rights, contracts, family, and land affects various aspects of people's lives, including social stability, the economy, and individual welfare. From the literature review, it was found that legal certainty and effective access to civil justice contribute significantly to improving the quality of life of people in big cities. Conversely, ineffective civil law enforcement can lead to uncertainty, conflict, and inequality that negatively affect people's welfare.